2004
DOI: 10.1038/sj.npp.1300460
|View full text |Cite
|
Sign up to set email alerts
|

Role of Neuroactive Steroid Allopregnanolone in Antipsychotic-like Action of Olanzapine in Rodents

Abstract: Olanzapine increases brain allopregnanolone (ALLO) levels sufficiently to modulate neuronal activity by allosterically regulating GABA A receptors. Recently, we reported the antipsychotic-like profile of ALLO in rodents. The present study examined the hypothesis that olanzapine-induced elevation of endogenous neurosteroid ALLO is vital for its neuroleptic-like action. The conditioned avoidance response (CAR) and apomorphine-induced climbing behavioral paradigms were used in rodents. Administration of ALLO (1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 102 publications
0
32
0
Order By: Relevance
“…For example, both clozapine (Marx et al, 2003;Barbaccia et al, 2001) and olanzapine (Marx et al, 2000a(Marx et al, , 2003 dose dependently elevate the neuroactive steroid allopregnanolone in rodent brain, and we have hypothesized that neuroactive steroid induction may contribute the therapeutic efficacy of these compounds (Marx et al, 2003(Marx et al, , 2005. Furthermore, recent data support the possibility that allopregnanolone potentiates olanzapine actions on dopamine-mediated behaviors in rodents (Ugale et al, 2004). In addition to certain antipsychotics, fluoxetine also elevates allopregnanolone levels in animal models (Uzunov et al, 1996;Pinna et al, 2003Pinna et al, , 2004, and these increases have been linked to its antidepressant-like effects in rodent behavioral models (Khisti and Chopde, 2000a;Khisti et al, 2000b) and to the mitigation of aggression in socially isolated rats (Pinna et al, 2003).…”
Section: Introductionmentioning
confidence: 52%
“…For example, both clozapine (Marx et al, 2003;Barbaccia et al, 2001) and olanzapine (Marx et al, 2000a(Marx et al, , 2003 dose dependently elevate the neuroactive steroid allopregnanolone in rodent brain, and we have hypothesized that neuroactive steroid induction may contribute the therapeutic efficacy of these compounds (Marx et al, 2003(Marx et al, , 2005. Furthermore, recent data support the possibility that allopregnanolone potentiates olanzapine actions on dopamine-mediated behaviors in rodents (Ugale et al, 2004). In addition to certain antipsychotics, fluoxetine also elevates allopregnanolone levels in animal models (Uzunov et al, 1996;Pinna et al, 2003Pinna et al, , 2004, and these increases have been linked to its antidepressant-like effects in rodent behavioral models (Khisti and Chopde, 2000a;Khisti et al, 2000b) and to the mitigation of aggression in socially isolated rats (Pinna et al, 2003).…”
Section: Introductionmentioning
confidence: 52%
“…While some studies show that DHEA or DHEAS therapy improves some symptoms in schizophrenia (48)(49)(50), other studies reveal that low levels of these NASs may be beneficial for patients (44). Determining which symptoms improve and which get worse with DHEA and (or) DHEAS therapy and assessing each patient's symptom profile and primary pathological changes in the brain will determine which patients would benefit from DHEA therapy.…”
Section: The Antipsychotic Potential Of Nassmentioning
confidence: 99%
“…Kumar and co-workers (Kumar et al 2005;Ugale et al 2004) reported that muscimol-stimulated LORR was changed by PKC modulators and suggested that the mechanism involved modulation of PKC-mediated phosphorylation of GABA-A receptor. In our study, PKC phosphorylation was not altered by HALO-FLU, so this mechanism cannot explain the effect of this treatment on muscimol-induced LORR, and involvement of other receptors, such as serotonin and dopamine, is suggested.…”
Section: Behavioral Effectmentioning
confidence: 98%
“…The onset and the cessation of muscimol-induced sleep were assessed by presence of the righting reflex (LORR). Loss of LORR was defined as the inability to right three times in 1 min after placement in the supine position in a V-shaped support and its return as the ability of the animal to right itself three times in 1 min (Kumar et al 2005;Ugale et al 2004). …”
Section: Loss Of Righting Reflex Testmentioning
confidence: 99%